On the Lookout for Dialogue: Towards an Extended Dialogism - Linell, Per (Public Journal of Semiotics, 2022)
What is dialogue and where can we search for it? This is the major question asked in this article, with the intention to contribute to a discussion of the essence of extended dialogism (ED), the study of dialogue in a broad perspective. I begin with a brief summary of ED formulated in 18 points, and then elaborate on some of these, including the relation between basic utterances (actions) and activity types, between literal and extended (metaphorical) notions of dialogue, and between descriptive and normative dialogism. I argue that ED has the potential to highlight interesting aspects of these issues, and illustrate with relevant examples, concluding with that of the ongoing war of the Russian Federation and its dictator, Vladimir Putin, against the people of Ukraine.